Yabancı Dil Olarak Dijital Türkçe Öğretimi - NACAKÇIOĞLU, Ali (Sakarya Üniversitesi Yayınları, 2023)
With the onset of integration of web technologies into our lives, a global transformation process has been triggered and traditional approaches have tended to evolve into digital organisms as a past aspect of the millennium line. The one-way information transfer process, which was activated with the Web 1.0 era, took root on the basis of content sharing and 'collaboration' with Web 2.0, and was characterized in a 'smart' and 'individualized' form with the Web 3.0, and eventually ended up searching for an artificial intelligence-oriented direction. The developments in machine learning, deep learning, and natural language processing algorithms, on the other hand, were crowned with the Web 4.0 technology, and the artificial intelligence-based virtual reality atmospheres became the center of attention as the new phenomenon of digital. As far as the relevant perspective is concerned, it is possible to say that today's modernization standards are shaped within the framework of technology. While the parameters of the 'new generation world' are built on the digital plane, the 'new generation of people' generations develop specifically in the skills of this plane.